Towards a classification of maximal peak-pit Condorcet domains - Guanhao Li; Clemens Puppe; Arkadii Slinko (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2020)
In this paper, we classify all maximal peak-pit Condorcet domains of maximal width for n È 5 alternatives. To achieve this, we bring together ideas from several branches of combinatorics. The main tool used in the classification is the ideal of a domain. In contrast to the size of maximal peak-pit Condorcet domains of maximal width themselves, the size of their associated ideal is constant.
Keywords: 330